My super sleepover book - Aber, Linda Williams (New York : Pocket Books, 1999)
Provides instructions on how to have a sleepover including recipes.
"A Minstrel book."
"A Parachute book."
"Based on the hit Warner Bros. TV series"--Cover.
"Warner World Wide Pub."
5.4
3-6.
Keywords: Children's parties -- Juvenile literature; Cooking -- Juvenile literature; Sleepovers -- Juvenile literature; Children's parties; Cooking; Sleepovers; Children's parties; Cooking; Sleepovers